2021
DOI: 10.1029/2021wr030380
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation of the Suspended Sediment Deposition in the Channel With Vegetation and Its Relevance to Turbulent Kinetic Energy

Abstract: The aquatic vegetation patch plays a significant role on sediment net deposition in the vegetated channels. Particularly, the flow is decelerated at the leading edge of a patch that tends to induce vertical updraft, that is, a diverging flow region, in which vegetation greatly affects the pattern of sediment net deposition. This study focuses on the simulation of the sediment net deposition in the whole vegetation patch region through an innovative random displacement model, a Lagrange method, with probability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Our results support previous conclusions that vegetation coverage is the most important factor affecting the lift-off velocity (LV) of seeds [37]. Secondly, the physical obstruction caused by plants or the surface matrix, which hinders diaspore movement [24,25,[40][41][42][43]. Our results showed that diaspores with balloon, discoid, thorn, two wings, and four wings exhibited lower lift-off velocities in V 3 than in V 2 .…”
Section: Effect Of Vegetation Structure On Diaspore Lift-off Velocity...supporting
confidence: 90%
“…Our results support previous conclusions that vegetation coverage is the most important factor affecting the lift-off velocity (LV) of seeds [37]. Secondly, the physical obstruction caused by plants or the surface matrix, which hinders diaspore movement [24,25,[40][41][42][43]. Our results showed that diaspores with balloon, discoid, thorn, two wings, and four wings exhibited lower lift-off velocities in V 3 than in V 2 .…”
Section: Effect Of Vegetation Structure On Diaspore Lift-off Velocity...supporting
confidence: 90%
“…The flow passing through the mobile sand bed with vegetation can be fundamentally regarded as a vegetated flow problem with temporally changing boundary conditions (Huai et al, 2021;Yang et al, 2021). Here, the most intense scouring test under the condition of Q = 1.8 L/s is selected for exploring the variation of the drag coefficient with time Figure 11 shows the change of the bed-load transport rate Q s over time under the condition of Q = 1.8 L/s and ∅ = 0.1, that is, test R4.3.…”
Section: Temporal Variation and The Approach To The Stable Drag Coeff...mentioning
confidence: 99%
“…Typically, SAV occurs in patches, introducing additional drag to water body and generating vegetation-induced turbulence (Tang et al 2019, Xu and. This turbulence profoundly alters the distribution of turbulence and affects the dynamics of sediment transport, erosion, resuspension, and deposition (Vastila 2016, Yang and Nepf 2019, Yang et al 2021.…”
Section: Introductionmentioning
confidence: 99%